Effect of Cesium Seeding on the Production of H– Ions in a Magnetized Sheet Plasma Source - Villorente, L. M. M.; Noguera, V. R.; Ramos, H. J. (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
The effect of the addition of cesium on the production of negative hydrogen ions (H–) in a magnetized sheet plasma source (SPNIS) is investigated. Plasma parameters and H– yields were determined from Langmuir probe and E x B probe measurements, respectively. Significant increase on H– yield is observed with the addition of a controlled flux of neutral Cs vapor. The maximum enhancement of 88 times compared with the uncesiated case is extracted at 5 cm away from the sheet plasma core at a discharge current of 0.5 A and initial gas filling pressure of 9 mTorr. The value is increased from 5.51 x 10–8 A/m2 for the uncesiated case to 4.86 x 10–6 A/m2 for the cesiated case. The largest negative hydrogen ion current density extracted is 0.0155 A/m2 at 2.5 A discharge current, 9 mTorr initial gas filling pressure, and 1 cm probe distance from the plasma center. Here, enhancement is only 9.8 times compared with pure hydrogen discharge. The increase in H– current density is attributed mainly to the cooling effect of Cs as evidenced by the considerable decrease in electron temperature especially at the periphery of the plasma.